The Analysis of Tsunami Hazard and Determination of Evacuation Routes Based on GIS in Coastal Areas (Case Study: Pacitan District, Pacitan Regency) - Huda, Muhammad Badrul; Ibrahim, Mohd Hairy; Jumadi, Jumadi (International Journal for Disaster and Development Interface, 2023)
The south of Java is a vulnerable to tsunami disasters. Pacitan District is a coastal area in the south of Java, which is directly adjacent to the Indian Ocean. Its location, which is directly adjacent to the Indian Ocean, is one of the areas that is prone to tsunami disasters. The purpose of this study were to analyze the spatial distribution of the tsunami hazard in the Pacitan District Coastal area under the 8.0 Mw earthquake scenario and to model the optimal evacuation route for handling the tsunami disaster in Pacitan District. Tsunami wave modeling uses Delft3D-Flow software, which is based on the Shallow Water Equations and Hloss calculations to determine the inundation area. Using GIS with the Least-Cost Path method to determine the optimal path for tsunami evacuation. The results showed that the tsunami wave height on the coastline was 5 meters high. A total area of 571.79 hectares of tsunami-affected area. The inundation area for each affected area is 239.70 ha in Sidoharjo Village, 190.87 ha in Ploso Village, and 141.22 ha in Kembang Village. Determination of evacuation routes obtained five evacuation routes. The travel time for the evacuation process with walking takes more than 30 minutes, whereas using a motorized vehicle is less than 10 minutes.